Sustainable Development Goals: The Crème de la Crème Nexus to Enhance Indonesian Enterprise’s Environmental Responsibility (Pandecta Research Law Journal, 2022)
Humanity is on the verge of the 2030 Agenda for Sustainable Development deadline. The tension between environmental and corporate-developmental interests has been a focal part of the law- and policy-making processes. These instruments reveal that the sustainable development agenda in the business and environmental sector has not been straightforward to accomplish. The balance, nonetheless, appears to bend in favor of securing the environment. This paper investigates how the “well-established” SDGs have matured as the nexus and affect the augmentation of the national corporate and environmental laws. In that respect, this work has delineated SDGs as a nexus for legislative improvement, proposed the possibility for mutuality with national corporate and environmental laws, and outlined the challenges impeding the purposeful implementation of SDGs. The purposes of this research are identifying the nexus between the SDGs and enterprise sustainability, to unravel the possibility for mutualism, and understanding the challenges hindering the implementation of SGDs in enterprises’ activities. The normative juridical legal research was administered for this research, with a literature study approach to compile scientific literacy from within and outside the country. The analysis is conducted qualitatively. This study establishes and ascertains that the SDGs are the ultimate nexus for business-environmental sustainability that can be accustomed to the local wisdom of each nation, notwithstanding it is universal in nature. The mutuality within the SGDs and business-environmental law can also be accomplished, and there is urgent merit to surmount the challenges that have been outlined in this paper.